2023
DOI: 10.1101/2023.07.31.549909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intramolecular feedback regulation of the LRRK2 Roc G domain by a LRRK2 kinase dependent mechanism

Abstract: The Parkinson's Disease (PD)-linked protein Leucine Rich Repeat Kinase 2 (LRRK2) consists of seven domains, including a kinase and a Roc G domain. Despite the availability of several high-resolution structures, the dynamic regulation of its unique intramolecular domain stack is nevertheless still not well understood. By in-depth biochemical analysis, assessing the Michaelis-Menten kinetics of the Roc G domain, we have confirmed that LRRK2 has similar to other Roco protein family members a KM value of LRRK2 tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…We and others have previously shown that the Roc domain of LRRK2 is subject to autophosphorylation at multiple sites, which are in proximity to the dimerization interface within the Roc-COR module (Gloeckner et al, 2010; Greggio et al, 2009; Helton et al, 2021). Furthermore, we recently identified a novel intramolecular feedback regulation of the LRRK2 Roc G domain that depends on auto-phosphorylation of the G1+2 residue (T1343) in the Roc P-loop motif (Gilsbach et al, 2023). In contrast to wild-type, ATP dependent monomerization is abolished for T1343A, suggesting it plays a key role in regulating auto-phosphorylation dependent monomerization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that the Roc domain of LRRK2 is subject to autophosphorylation at multiple sites, which are in proximity to the dimerization interface within the Roc-COR module (Gloeckner et al, 2010; Greggio et al, 2009; Helton et al, 2021). Furthermore, we recently identified a novel intramolecular feedback regulation of the LRRK2 Roc G domain that depends on auto-phosphorylation of the G1+2 residue (T1343) in the Roc P-loop motif (Gilsbach et al, 2023). In contrast to wild-type, ATP dependent monomerization is abolished for T1343A, suggesting it plays a key role in regulating auto-phosphorylation dependent monomerization.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, we could show that the kinetical properties of LRRK2-mediated GTP hydrolysis are negatively regulated by auto-phosphorylation (Gilsbach et al, 2023). To assess if this negative feedback is mediated via LRRK2 monomerization-dimerization, we auto-phosphorylated the purified protein under conditions allowing sufficient phospho-transfer (Gloeckner et al, 2010) and analyzed its oligomeric state.…”
Section: Autophosphorylation Induces Lrrk2 Monomerizationmentioning
confidence: 99%
“…PD-associated mutations in LRRK2 are concentrated in the catalytic Roc-COR and kinase domains, and commonly lead to an increase in kinase activity and - depending on the experimental set-up - a decrease in GTPase activity (Kalogeropulou et al, 2022; Lewis et al, 2007; West et al, 2005). Moreover, recent data also suggest a reciprocal cross-talk between both catalytic activities (Gilsbach et al, 2023; Störmer et al, 2023; Weng et al, 2023). Nevertheless, while the therapeutic targeting of the LRRK2 kinase domain has been a major focus of research in the last two decades, the regulation and targeting of the Roc-COR domains is only recently gaining more attention (Cogo et al, 2022; Helton et al, 2021; Park et al, 2022; Pathak et al, 2023).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, recent data also suggest a reciprocal cross-talk between both catalytic activities (Gilsbach et al, 2023;Störmer et al, 2023;Weng et al, 2023). Nevertheless, while the therapeutic targeting of the LRRK2 kinase domain has been a major focus of research in the last two decades, the regulation and targeting of the Roc-COR domains is only recently gaining more attention (Cogo et al, 2022;Helton et al, 2021;Park et al, 2022;Pathak et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…PD-associated mutations in LRRK2 are concentrated in the catalytic Roc-COR and kinase domains, and commonly lead to an increase in kinase activity and -depending on the experimental set-upa decrease in GTPase activity (Kalogeropulou et al, 2022 ;Lewis et al, 2007 ;West et al, 2005 ). Moreover, recent data also suggest a reciprocal cross-talk between both catalytic activities (Gilsbach et al, 2023 ;Störmer et al, 2023 ;Weng et al, 2023 ). Nevertheless, while the therapeutic targeting of the LRRK2 kinase domain has been a major focus of research in the last two decades, the regulation and targeting of the Roc-COR domains is only recently gaining more attention (Cogo et al, 2022 ;Helton et al, 2021 ;Park et al, 2022 ;Pathak et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%